Proposity study and effects on mechanical properties of discontinuous reinforced metal matrix composite (DRMMC) - Syed Ahmad, Syarifah Nur Aqida (2004)
The effects of porosity on mechanical properties of cast discontinuous reinforced meta] matrix composite (DRMMC) were investigated. Hence, a casting rig was fabricated to produce DRMMCs via conventional and modified stir casting method . The modified stir casting method performed pre-heating of reinforcement particles during matrix alloy melting. Silicon carbide particle reinforced aluminium alloy composites were produced with three different stirring speeds: 100, 200 and 500rpm. Cast DRMMCs were evaluated in as-cast condition for microstructure analysis, porosity and density measurement and mechanical testing. The mechanical properties of cast DRMMC were determined from tensile and fatigue tests conducted at room temperature. Tensile tests were referred to ASTM B557 standard while the axial fatigue test (ASTM E466) was conducted at stress ratio (R) of -1. A finite element method (FEM) analysis was carried out using Solidworks 2003 software. It was found that the major causes of porosity occurrence in cast DRMMC were clustered silicon carbide particles, gas entrapment and solidification shrinkage. From porosity measurement, conventionally stir cast DRMMCs contained higher porosity compared to the modified stir cast DRMMCs. The least content of porosity evaluated is at 0.09% in modified stir cast DRMMC, while the highest is at 12.45% in conventionally stir cast DRMMC. Fatigue strength (at 1 x 107 cycles) of cast DRMMCs at 5, 10, and 15% reinforcing SiC particle were 129.7, 141.5 and 157.3 MPa respectively. Based on the FEM analysis, porosity in conventionally stir cast DRMMC promotes higher von Mises stress as much as 40.2 MPa compared to 12.6 MPa in modified stir cast DRMMC. The porosity contents increased with increasing silicon carbide particles. Higher stirring speed tended to entrap more gas during mixing, whereas a lower stirring speed was ineffective to disperse SiC particles and results in clustering. Increasing porosity content in cast DRMMC had decreased the density and tensile properties ofDRMMC as depicted by the FEM analysis. Though, fatigue strength increased as a result of existing constraints in form of porosity